Peran Hukum Adat dalam Penyelesaian Sengketa Tanah di Masyarakat Desa Sesela - Maulana Ibrahim; Anggara Kusuma; Ma’rifatullah Ma’rifatullah (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
Sesela Village is one of the areas that still upholds local wisdom values and customary legal institutions in the community’s social life. Land disputes in this region are generally resolved through customary mechanisms before resorting to the formal state legal system. This study employs a qualitative approach using a case study method, through in-depth interviews, observation, and documentation involving customary leaders, village officials, and community members involved in the dispute resolution process. The findings indicate that customary law plays a significant role as a means of resolving agrarian conflicts in a preventive and solution-oriented manner. The presence of customary figures, such as traditional elders and religious leaders, functions as trusted mediators for the disputing parties. The customary land dispute resolution mechanism emphasizes not only aspects of positive law but also upholds values of deliberation, peace, and social balance. However, there are challenges in harmonizing customary law with national law, particularly regarding the formal legal recognition of customary settlements. This study recommends strengthening the synergy between village governments, customary institutions, and state legal bodies to create a fair and sustainable land dispute resolution system.